Pengaruh Pembelajaran PAI, Pola Asuh Orang Tua, Dan Budaya Religiusitas Sekolah Terhadap Kedisiplinan Beribadah Siswa di SMPIT Hayatan Thayyibah dan SMPITQ Al-Fath Kota Sukabumi - Endin Nasrudin; Istikhori; Abiyyu Naufal Malik (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
This study aims to find out how the influence of PAI learning, parenting parents, and school religiosity culture has on the discipline of worship. The research method used in this research is a quantitative survey and correlational method. The population was taken from two accredited A schools, namely SMPIT Hayatan Thayyibah and SMPITQ Al-Fath Sukabumi City. As a representative sample of students studied were 426 classes VIII and XI with a research sample of 100 respondents. Data collection was taken using a questionnaire. Based on the results of the research that has been done, it can be concluded that there is a positive influence on PAI learning, parenting parents, and school religiosity culture on religious discipline with a coefficient of determination (ry123Â²) of 0.642. So the increase in the discipline of worship is the result of a process from the PAI learning variables, parenting styles and school religiosity culture. Keywords: PAI Learning; Parenting Style; School Religiosity Culture; Student Worship Discipline